Vascular endothelial growth factor mRNA levels as a biomarker for short‐term N‐butyl‐N‐(4‐hydroxybutyl) nitrosamine‐induced rat bladder carcinogenesis bioassay. Issue 2 (28th May 2014) - Wakui, Shin; Mutou, Tomoko; Takahashi, Hiroyuki; Ikegami, Masahiro; Wanibuchi, Hideki; Fukushima, Shoji
ABSTRACT Generically, carcinogenic effects of chemicals in bladder carcinogenesis are judged by induction of papillary or nodular (PN) hyperplasia in rats given N‐butyl‐N‐(4‐hydroxybutyl) nitrosamine (BBN) for 4 weeks and the test chemical for 22–28 weeks. However, upregulation of vascular endothelial growth factor (VEGF) begins early in rat BBN bladder carcinogenesis. To establish a short‐term rat bladder carcinogenic bioassay, we analyzed the correlations between VEGF, VEGF mRNA and bladder lesions inductions at 10 and 26 weeks after BBN treatment. Six‐week‐old male Wistar (slc) rats were given 0.05% BBN for 4, 10 or 26 weeks. To avoid individual rat bias, the bladders were investigated by partial cystectomy at 10 weeks and total cystectomy at 26 weeks. After induction, PN hyperplasia and carcinoma in rats increased with the length of BBN treatment and immunohistochemical VEGF expression also increased following carcinogenesis, but the immunoreactivity of individual lesions was quite variable. Moreover, induction of PN hyperplasia at 10 weeks' BBN treatment was not significantly correlated with that at 26 weeks' treatment; thus, it was not possible to predict the carcinogenic effect due to the induction of PN hyperplasia at 26 weeks' BBN treatment by that at 10 weeks' treatment. However, VEGF mRNA levels of rat bladders at 10 weeks' BBN treatment revealed a strong significant correlation with the incidence of bladder lesions at 26 weeks' treatment. Here, we suggest that quantitative VEGF mRNA levels are a good biomarker for a short‐term BBN‐induced bioassay for rat bladder carcinogenesis. Copyright © 2014 John Wiley & Sons, Ltd.